IMPROVING NINTH GRADE STUDENTS’ COMPREHENSION IN LEARNING INDONESIAN LANGUAGE BY IMPLEMENTING PEER-TUTOR STRATEGY IN SMP N 2 BINTAN - Ruslan Manurung (SALEE: Study of Applied Linguistics and English Education, 2020)
This research was based on the ninth grade students’ lack of ability in using Indonesian language at SMP N 2 Bintan which it was supported by the number of students with passed-scores not more than 50%. As a teacher and also a researcher as well, the daily observation showcased students’ problems are being shy to ask and afraid of questioning in the classroom. Considering these in mind, Classroom Action Research (CAR) was conducted by implementing Peer Tutor Strategy as part of cooperative learning. The data collection method was a learning achievement test. The data were analysed and explained in descriptive way. The results of the study revealed Peer Tutor Strategy can improve student learning achievement. It was proved by the improvement of students’ scores in two cycles. In the first cycle, the average score is 63.75 while in the second cycle is 80. From this significant improvement, the implementation of Peer Teaching Strategy is effective in improving students’ Indonesian Language ability.